A Língua Brasileira de Sinais como elemento constitutivo da inclusão de alunos surdos - ALMEIDA, Lucineide Leal Silveira de (2022)
This study aims to address the importance of the teaching of the Brazilian Language-Libras as a peculiar element in the schooling of the deaf children, supported by Law 10,436/02, with the main focus being their inclusion in the school context, in order to understand how the process of inclusion of the disabled child in public educational institutions happens and in some way contribute to it. Initially, the educational history of the deaf people was approached to obtain a broad vision of the challenges and struggles they have gone through, stating that, without prior knowledge, there is no meaningful learning. It was verified that the deaf when entering the inclusive regular school, is not assisted according to their cognitive peculiarities, inhibiting them from devising formative experience that school institutions should offer to all. In this sense, inclusive education and the bilingual school are addressed, since it is important to complement the training curriculum of professionals who work in schooling in order to subsidize the deaf student learning quality. The use of the Portuguese Language assumes a position of L2, for the deaf students, in the execution of the school curriculum. It is concluded that the Brazilian Language must be acquired by the deaf, naturally (in the case of deaf children of deaf parents) or taught to them with an appropriate approach and methodology (especially for those children of hearing parents who do not dominate the sign language). Libras, as the official language of Brazil, must also be diffused, not only in schools, but in all instances of society.